In search of WTO trade effects : preferential trade agreements promote trade strongly, but unevenly - Eicher, Theo S. (IMF WashingtonUS, 2009)
Shows in this paper that WTO does not boost trade among its members, rather, regional and bilateral preferential agreements strongly influence trade flows.